Exploring the Science of Marma - An Ancient Healing Technique: Marma in Yoga and Other Ancient Indian Traditions - Alka Mishra; Vandana Shrivastava (Dr. Chinmay Pandya, 2022)
Marma Science is an extremely important branch of Ayurveda. Marma points are important vital places in the body, that are the 'seats of life' (Prana - the vital life force). As any injury to these parts may lead to severe pain, disability, loss of function, loss of sensation, or death, therefore, they hold an important place in the science of surgery, wherein they are considered 'Shalya Vishayardha' (half of the entire science of surgery). The ancient scriptures have strictly directed against causing any injury to these vital spots. However, recent research have attempted the stimulation of Marma points for therapeutic benefits, with encouraging outcomes. In view of these mutually conflicting, importance applications of Marma Science, the present study was undertaken for its in-depth study. Part-1 of this study presented information about different aspects of Marma Science in various ancient / classical Indian scriptures. Part-2 gave a detailed description of the number of marmas, their location, structures involved, classification, the effect of trauma, etc., as per classical texts, as well as correlation with modern science. The present article, which is part-3 of this study, explores the use of Marma Science in Yoga and other ancient Indian traditions. It is observed that various Yogic practices had been devised with the primary aim of stimulating specific Marma points, with important healing applications. Several ancient Indian traditions used Marma Science both as a martial art for self-defense and inflicting injury on the opponents, and as a therapeutic technique for healing purposes.